Thermal Sunyaev–Zel’dovich Effect in the Circumgalactic Medium. I. Detection, and a Surprising Pattern in Self-similarity and Baryon Sufficiency - Sanskriti Das; Yi-Kuan Chiang; Smita Mathur (The Astrophysical Journal)
We report on the measurement of the thermal Sunyaev–Zel’dovich (tSZ) effect in the circumgalactic medium (CGM) of 641,923 galaxies with M _⋆ = 10 ^9.8–11.3 M _⊙ at z < 0.5, pushing the exploration of the tSZ effect to lower-mass galaxies compared to those in previous studies. We cross-correlate the galaxy catalog of the Wide-field Infrared Survey Explorer and SuperCOSMOS with Compton- y maps derived from the combined data of the Atacama Cosmology Telescope and Planck. We improve on the data analysis methods (correcting for cosmic infrared background and Galactic dust, masking galaxy clusters and radio sources, stacking, and employing aperture photometry), as well as modeling (taking into account beam smearing, the “two-halo” term, and any zero-point offset). We constrain the thermal pressure in the CGM of M _⋆ = 10 ^10.6–11.3 M _⊙ galaxies for a generalized Navarro–Frenk–White profile and provide upper limits for M _⋆ = 10 ^9.8–10.6 M _⊙ galaxies. The relation between M _500 (obtained from an empirical M _⋆ – M _200 relation and a concentration factor) and ${\tilde{Y}}_{R500}^{sph}$ (a measure of the thermal energy within R _500 ) is >2 σ steeper than the self-similarity relation and the deviation from the same that has been reported previously in higher-mass halos. We calculate the baryon fraction of the galaxies, f _b , assuming the CGM to be at the virial temperature that is derived from M _200 . The baryon fraction f _b exhibits a nonmonotonic trend with mass, with M _⋆ = 10 ^10.9–11.2 M _⊙ galaxies being baryon-sufficient.